The effectiveness of various control strategies: An insight from a comparison modelling study. (21st September 2022) - Zhou, Weike; Bai, Yao; Tang, Sanyi
Highlights: A novel mathematical model is proposed to describe the heterogeneity of control interventions. Xi'an presents a lower transmission probability but a higher reproduction number. Enhancing closed-off management, tracing and testing intensities, are effective. Citywide lockdown is not essential when the closed-off management is strictly implemented. Enhancing tracing strategy is more effective than enhancing testing strategy in the early stage. Abstract: Several local outbreaks have occurred and been suppressed with the dynamic zero-COVID policy and widely promoted vaccination program implemented in China. The epidemic duration and final size vary significantly in different cities, which may be attributed to different implementation patterns and intensities of non-pharmaceutical interventions (NPIs). It's important to capture the underlying mechanism to explore more efficient implementation patterns of NPIs in order to prevent the future resurgence. In this study, outbreaks caused by Delta variant in Xi'an, Yangzhou and Guangzhou in 2021 are chosen as the examples. A novel model dividing the population into three groups is proposed to describe the heterogeneity of control interventions. The model is calibrated and key parameters related to NPIs are estimated by using multi-source epidemic data. The estimation results show a lower transmission probability but a higher initial reproduction number in Xi'an. Sensitivity analysis are conducted to investigate the impact of various control measures in different epidemic phases. The results identify the vital role of enhancing closed-off management, strengthening tracing and testing intensities, on shortening the epidemic durations and reducing the final size. Further, we find that sufficiently implemented closed-off management would prevent the city from lockdown. Strengthening the tracing other than the testing strategy in the initial stage is more effective on containing the epidemic in a shorter duration with less infections.